Evaluating Significant Factors of Graduate Students’ Satisfaction With Small Private Online Course in Chongqing, China - Jian, Zhang (Scholar: Human Sciences, 2024)
Purpose: The objective of this research is to investigate the determinants that impact student satisfaction when utilizing Small Private Online Courses (SPOCs) in Chongqing, China. The conceptual framework encompasses factors such as information quality, system quality, service quality, perceived ease of use, perceived usefulness, perceived enjoyment, interactivity, and satisfaction. Research design, data, and methodology: The research focused on a target population comprising 500 graduate students specializing in art, enrolled in the SPOC programs of the two prominent universities situated in Chongqing, China. Employing a quantitative approach, data collection was carried out through a structured questionnaire-based research design. To ensure the quality of the data, the study applied the Index of Item-Objective Congruence (IOC) and Cronbach's Alpha for assessing content validity and data reliability, respectively. The gathered data underwent analysis using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) techniques. Results: The results show that information quality, system quality, perceived ease of use, and perceived usefulness significantly influence satisfaction. Perceived ease of use has a significant influence on perceived usefulness. Nevertheless, service quality, interactivity and perceived enjoyment have no significant influence on satisfaction. Conclusions: The findings offer practical insights for educators and institutions aiming to improve the quality and effectiveness of online education in Chongqing, China, and beyond.